Making work visible ethnographically grounded case studies of work practice - Szymanski, Margaret H.; Whalen, Jack, 1949-; ebrary, Inc. (Cambridge ; New York : Cambridge University Press, 2011)
"In the 1970s, Xerox pioneered the involvement of social science researchers in technology design and in developing better ways of working. The Xerox legacy is a hybrid methodology that combines an ethnographic interest in direct observation in settings of interest with an ethnomethodological concern to make the study of interactional work an empirical, investigatory matter. This edited volume is an overview of Xerox's social science tradition. It uses detailed case studies that show how the client engagement was conducted over time and how the findings were consequential for business impact. Case studies in retail, production, office, and home settings cover four topics: practices around documents, the customer front, learning and knowledge-sharing, and competency transfer. The impetus for this book was a 2003 Xerox initiative to transfer knowledge about how to conduct ethnographically grounded work-practice studies to its consultants so that they may generate the kinds of knowledge generated by the researchers themselves"--
Machine generated contents note: Introduction Margaret H. Szymanski and Jack Whalen; Part I. Work Practice Study in Historical Context: 1. Work practice and technology: a retrospective Lucy Suchman; 2. Engineering investigations: what is made visible in making work visible? Wes Sharrock and Graham Button; Part II. Applying Work Practice Methods: 3. Uncovering the unremarkable Peter Tolmie; 4. Work practices to understand the implications of nascent technology Francoise Brun-Cottan and Patricia Wall; 5. Tokyo to go: using field studies to inform the design of a mobile leisure guide for Japanese youth Diane J. Schiano and Victoria Bellotti; Part III. Practices around Documents: 6. Exploring documents and the future of work Jennifer Watts-Perotti, Mary Ann Sprague, Patricia Wall, Catherine McCorkindale, Lisa Purvis, and Gabriele McLaughlin; 7. New ways of working: the implications of work practice transitions Mary Ann Sprague, Nathaniel Martin, and Johannes A. Koomen; 8. Behind the scenes: the business side of medical records Nathaniel Martin and Patricia Wall; 9. Seeing the right colour: technical and practical solutions to the problem of accurate colour reproduction in the digital print industry Tommaso Colombino, David Martin, Jacki O'Neill, Mary Ann Sprague, Jennifer Watts-Perotti, Jutta Willamowski, Frederic Roulland, and Antonietta Grasso; Part IV. The Customer Front: 10. Integrated customer service: re-inventing a workscape Jack Whalen and Marilyn Whalen; 11. Interactions at a reprographics store Erik Vinkhuyzen; 12. Ethnography-inspired technology for remote help-giving Jacki O'Neill, Peter Tolmie, Stefania Castellani, Antonietta Grasso, and Frederic Roulland; 13. Sign of the times at the department store: replacing paper with electronic signs Johannes A. Koomen; Part V. Learning and Knowledge Sharing: 14. Communal knowledge sharing: the EUREKA story Jack Whalen and Daniel G. Bobrow; 15. Designing document solutions for airline maintenance advisories Patricia Wall and Johannes A. Koomen; 16. Transforming information system design: enabling users to design Yutaka Yamauchi; 17. Rethinking how projects are managed: meeting communication across the organizational hierarchy Erik Vinkhuyzen and Nozomi Ikeya; Part VI. Competency Transfer: 18. Fujitsu learned ethnography from PARC: establishing the social science center Koji Kishimoto with a preface by Jack Whalen; 19. The work practice center of excellence Luke Plurkowski, Margaret H. Szymanski, Patricia Wall, and Johannes A. Koomen; 20. Transferring ethnographic competence: personal reflections on the past and future of work practice analysis Brigitte Jordan.
Electronic reproduction.
Keywords: Xerox Corporation -- Management; Xerox Corporation -- Employees; Organizational learning -- Case studies; Knowledge management -- Case studies; Human engineering -- Case studies; Work -- Social aspects -- Case studies; Electronic books